Efektifitas Layanan Bimbingan Kelompok Melalui Teknik Sosiodrama dalam Meningkatkan Perilaku Disiplin Siswa SMP Negeri 3 Ingin Jaya Aceh Besar - Zulmairi, Zulmairi; Khaira, Wanty (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
Discipline is a behavior that shows adherence to rules and a mental attitude to do something at the right time while respecting time. However, at the state junior high school Ingin Jaya, there are some students who exhibit low levels of disciplinary behavior. This study aims to determine the effectiveness of group counseling services using the sociodrama technique to improve students' disciplinary behavior at Ingin Jaya Junior High School. This research uses a quantitative approach in the form of a one-group pretest-posttest design. The research subjects consist of 24 students selected using purposive sampling. Data collection was done using a questionnaire to measure students' disciplinary behavior levels, followed by a T-test analysis using SPSS version 22. Based on the data analysis results, the obtained T-hitung (16.418) is greater than the T-tabel (1.714), indicating a significant difference between before and after the group counseling service using the sociodrama technique was provided to improve students' disciplinary behavior. The results show that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It can be concluded that there is an improvement in students' disciplinary behavior after receiving group counseling services and the sociodrama technique